2003
DOI: 10.1046/j.1460-9592.2003.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of halothane and sevoflurane on QT dispersion in paediatric patients

Abstract: Neither sevoflurane nor halothane caused a significant increase in QTd compared with control values before induction. Only QTd following intubation was significantly greater in the halothane group than the sevoflurane group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…Therefore, it is most important to determine the effect of lidocaine on the detrimental effects of TI and anaesthetic agents on cardiac functions. The only trial evaluating the effects of TI on QTcd under sevoflurane anaesthesia was performed by Gurkan, et al 28) Similarly, in the present study the QTcd was also unchanged. One distinctive feature between the 2 studies is that they conducted their trial in paediatric patients.…”
Section: )supporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, it is most important to determine the effect of lidocaine on the detrimental effects of TI and anaesthetic agents on cardiac functions. The only trial evaluating the effects of TI on QTcd under sevoflurane anaesthesia was performed by Gurkan, et al 28) Similarly, in the present study the QTcd was also unchanged. One distinctive feature between the 2 studies is that they conducted their trial in paediatric patients.…”
Section: )supporting
confidence: 68%
“…Although the present study did not aim to evaluate the effects of sevoflurane in different types of surgery, it has been demonstrated that sevoflurane anaesthesia increased the QTc interval in laparotomic gynaecological surgery 26) but had no effect on the main haemodynamics during minor gynaecological surgeries. 27) Moreover, some have suggested that QTd and the QTcd are not affected 28) regardless of the severity and type of surgery. On the other hand, there are reports showing that all QT parameters (QT, QTc, QTd, and QTcd) 3) or 2 parameters such as QT and QTc 29) or QTd and QTcd 3) increased.…”
Section: )mentioning
confidence: 99%
“…Comparing the basal values of QT and QTc intervals of patients before induction with the measurements after 20 minutes of induction, no arrhythmia was observed to have developed in the patients, and the QTc interval did not exceed 440 milliseconds; however, it was suggested that sevoflurane significantly prolonged the QTc interval [12]. On the other hand, Gurkan et al reported that halothane and sevoflurane used for induction in pediatric patients caused various levels of abnormalities in ventricular repolarization following tracheal intubation, and that a greater increase of the QTd and QTcd values was observed in halothane following the intubation [13].…”
Section: Discussionmentioning
confidence: 95%
“…7,16,17 Acquired QT prolongation and increased dispersion have been found to be associated with an increase in sudden cardiac death as in long QT syndrome. [17][18][19] Tavernier et al found out that patients with ventricular fibrillation without underlying structural heart disease had abnormal repolarization behavior, characterized by an increased QTD. 18 Reversal of the increase in QTD by antiarrhythmic agents in patients with the long QT syndrome or dilated cardiomyopathy indicates that this parameter can be used as an efficacy measure in the treatment of serious arrhythmias.…”
Section: Discussionmentioning
confidence: 99%